2014
DOI: 10.2139/ssrn.2526066
|View full text |Cite
|
Sign up to set email alerts
|

Service Marketing Mix of Indian Hospitals: A Critical Review

Abstract: Sreenivas, Srinivasarao and Srinivasa (2013) said that "The health care market has become consumer centered and expecting high quality care at a reasonable price. The mushroomed development of corporate hospitals in India, competition is also bringing massive changes in industry structure. In this context, hospital services' marketing is slowly and surely coming of age and is being woven into the fabric of hospitals planning and public relations programmes." The essence of any marketing activity is marketing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Angoodet. Al., went further to comment on importance of a welldesigned physical healthcare facility that is attractive to patients/clients (25).…”
Section: Discussionmentioning
confidence: 99%
“…Angoodet. Al., went further to comment on importance of a welldesigned physical healthcare facility that is attractive to patients/clients (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, the elements that can affect patients differ between hospitals. This can happen because the marketing strategy must focus on consumers, and the company uses strategies appropriate to the market segment the company occupies to succeed (Armstrong et al, 2014); (Motwani & Shrimali, 2014). A good marketing strategy also has functions such as providing direction for the organization or program, focusing on one of the many options, unifying organizational actions, differentiating the organization from other organizations, distributing corporate promotional materials, managing corporate resources, supporting hospital decision-making, make the organization superior to other market competition, and demonstrate competence to external stakeholders (Thomas, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the study’s general finding showed that even though ownership seems to affect specific care dimensions, the high degree of professionalization neutralizes the effect that can be observed in the clinical results (Bøgh Andersen and Jakobsen, 2011). Motwani and Shrimali (2014) highlighted the differentiating role of transparency in medical tariffs, appropriate staff communication and high service quality, affecting service recipients’ preference, loyalty and satisfaction (Motwani and Shrimali, 2014). In addition, continuity of care has been severally considered the provision of high-quality services over time so that the clinical team cooperatively takes part in continuous health-care delivery toward the optimum benefit of patients.…”
Section: Discussionmentioning
confidence: 99%